PERAN BUDAYA LOKAL SEBAGAI MEDIA RESOLUSI KONFLIK - Ode, Samsul; Rachmawati, Nur Aini (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2017)
Conflict is one of the social phenomena that continues to exist in human life. Local culture plays an important role in the conflict management process. Local cultural values are believed to be an alternative in the phases of decreasing the intensity of the conflict. Indonesia as a country with a very high level of pluralis  has a lot of local culture which on one hand is able to become a media of conflict resolution although it must be recognized on the other hand also become the triggerf many social conflicts that bring up issues of SARA (Tribe, Nation, Race and Religion ). This study seeks to see how the relevance and role of local culture as amedia of social conflict resolution. Local cultural values can be used as a medium conflict resolution that exists at the local level although in reality, the changes and progress of the times continue to undermine local cultural values.Keywords: Conflict, Culture and Media